Assessment of market competition and financial stability of Takaful market in Saudi Arabia and Malaysia - Cheong, Sue Sim; Sheikh Hassan, Ahmad Fahmi (Inderscience Publishers, 2020)
The purpose of this study is two-fold: to examine the Takaful market structure in Saudi Arabia and Malaysia, as well as to investigate market competition and financial stability nexus from year 2008 until 2016. This paper inspected the market structure by using Herfindahl-Hirschman index (HHI) and four-firm concentration ratio (CR4), while Z-score was employed to evaluate the aspect of financial stability. The ordinary least square (OLS) estimator was applied to assess the market competition and financial stability nexus. The outcomes revealed that the Takaful markets in both countries started shifting to moderately-concentrated position from highly-concentrated markets. Regression results appeared to support competition-stability view and transmission mechanism hypothesis. The study findings have significant policy implications for designing and implementing regulations to enhance market efficiency and to safeguard the interests amongst policyholders, apart from promoting both the progression and stability of Takaful market in both countries.